Cracking the code of HBV persistence: cutting-edge approaches to targeting cccDNA in chronic hepatitis B with or without pyogenic liver Abscesses - Saeed, Umar; Piracha, Zahra Zahid; Khan, Mahmood; Tariq, Muhammad Nouman; Gilani, Syed Shayan; Raza, Muhammad; Munusamy, Rakshana; Bose, Naveen; Ozsahin, Dilber Uzun; Özşahin, İlker and Nauli, Surya M. (Frontiers in Medicine, 2025)
Chronic Hepatitis B Virus (HBV) infection remains a formidable global health challenge, driving severe liver complications such as hepatocellular carcinoma (HCC) and pyogenic liver abscesses (PLA). At the core of HBV persistence lies covalently closed circular DNA (cccDNA), a viral reservoir that fuels ongoing infection despite antiviral treatments. This review highlights molecular mechanisms governing cccDNA formation, maintenance, and clearance, spotlighting innovative therapeutic strategies to disrupt this key viral element. We explore cutting-edge approaches, including epigenetic modulation to silence cccDNA, RNA interference (RNAi) for viral RNA degradation, and CRISPR/Cas genome editing to excise cccDNA directly. Additionally, emerging antiviral therapies and immunotherapies, such as therapeutic vaccines and immune checkpoint inhibitors, offer new avenues for enhanced treatment efficacy. Special attention is given to the clinical complexities of managing HBV in patients with co-morbid conditions like HCC and PLA, emphasizing the necessity of a multidisciplinary approach. The interplay between antibacterial and antiviral therapies in PLA-associated HBV cases is critically examined to prevent treatment antagonism, ensuring optimal patient outcomes. Advanced therapeutic strategies, including nucleos(t)ide analogs, interferon therapy, and novel genomic interventions, are explored in both isolated HBV infection and PLA co-infections. Personalized regimens remain pivotal in enhancing therapeutic efficacy and long-term disease control. Current review advocates for a shift toward precision medicine, highlighting the critical need for interdisciplinary collaboration to bridge molecular discoveries with clinical innovations. Ultimately, these advancements promise to revolutionize the management of chronic HBV, paving the way for potential cures and improved patient outcomes.